Proses Pengembangan dan Evaluasi Sumber Daya Manusia Aparatur: Studi Kasus Dinas Lingkungan Hidup Kota Samarinda - Sabilatur Rosyidah; Amanda Putri Febrianti; Yashinta Nursalsabila; Rosida Yanti; Milasari Milasari; Nova Vatmawati; Enos Paselle (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2024)
This study aims to determine the development and evaluation of human resource apparatus at the Samarinda City Environment Agency. Human resources (HR) are valuable assets in an organization or agency. Therefore, the human element is the most important element that needs to be managed properly through planning, organizing, directing, monitoring and evaluating, so as to increase devotion, quality, expertise, skills and successful implementation of tasks in an efficient and effective manner in achieving organizational goals. This research uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results showed that the process and evaluation of human resource development of DLH apparatus was still heading towards the process stage of improving skills and knowledge through trainings such as technological guidance and training. In this improvement, obstacles were found in the form of budgeting needed in the implementation of technological guidance training (bimtek) and training. The educational background of employees which creates gaps in the implementation of cooperation, as well as the lack of motivation obtained through the provision of intensive also affect the improvement of the process of developing the quality of human resources in DLH Samarinda City.